Riddle Riddle - Martins, Sope (Nigeria, 2022)
Tamuno has the most annoying brother in the world! Abbey is never quiet and never does what he's told. But when he disappears into a mysterious hole in the ground one day, Tamuno goes after him without hesitation...
Keywords: Adventure; Juvenile Fiction; Riddle